Research on safety and compliance of imported microbial inoculants using high-throughput sequencing - Dong, Lin; Zhang, Zilong; Zhu, Biyun; Li, Shenwei; He, Yan; Lou, Yating; Li, Ping; Zheng, Huajun; Tian, Zhengan; Ma, Xia (Frontiers in Medicine, 2022)
Microbial inoculants are widely used in wastewater treatment, soil remediation and biological control. Safety and compliance for active constituents are considered to be the most important measures of imported microbial inoculants. Microbial inoculants composition was commonly identified by phenotypic culture, which is time-consuming and labor intense with occasionally false negative results provided, and can only be tested for specific species. High-throughput sequencing (HTS), known for its non-targeted detection of unknown species composition in samples, is suitable for composition consistency identification and biosafety analysis of imported microbial inoculants. In this study, application of HTS for microflora distribution and resistance gene were verified in microbial inoculants for environmental protection and then applicated in imported microbial inoculants. Both Illumina and Nanopore based HTS methods identified same dominant bacterial species successfully in the imported microbial inoculants. The main component bacterial species were Bacillus subtilis, Bacillus amyloliquefaciens, Bacillus licheniformis, and Enterococcus faecium, and further confirmed with traditional methods. The antibiotic resistance genes Bacillus subtilis mprF, bcrA, blt, lmrB, rphB, tet(L), tmrB, vmlR, ykkC and ykkD were detected in all samples. Our results indicated that HTS processes the application potential to identify the active ingredients of microbial inoculants. Therefore, rapid and accurate identification of the microbial compositions in microbial formulation products is of high importance for port biosafety supervision.